A Pd / Sn / SiO2-HTA catalyst, its preparation method and application

CN122912845APending Publication Date: 2026-10-16KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611402417.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,Pd基催化剂在实际应用中存在以下突出问题:(1)低温活性不足,甲烷完全转化温度通常高于400 ℃;(2)高温工况下PdO纳米颗粒易发生烧结团聚,导致催化剂快速失活;(3)抗水中毒能力差,反应体系中的水蒸气会吸附在活性位点上,与PdO反应生成低活性的Pd(OH)2,严重抑制催化活性,使其难以适配复杂恶劣的工况环境

Benefits of technology

[0016] This invention provides a method for preparing a Pd/Sn/SiO2-HTA catalyst. The method employs a stepwise impregnation method to prepare Pd/Sn/SiO2, followed by steam-induced treatment at 700-800 °C for 3-8 h. This overcomes the traditional bias that "hydrothermal aging leads to performance degradation" and achieves positive regulation of the active structure. The resulting catalyst exhibits excellent low-temperature activity (T0) in the catalytic combustion of methane. 50 With a temperature range of approximately 310℃, long-term stability (no deactivation at 350℃ for 70 h), and water resistance (slight decrease in activity at 5% H2O for 45 h with reversible recovery), it is suitable for the efficient purification of low-concentration methane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912845A_ABST
    Figure CN122912845A_ABST
Patent Text Reader

Abstract

The present application relates to the field of environmental catalysis and industrial catalysis technology, and particularly relates to a Pd / Sn / SiO2- HTA catalyst, a preparation method and application thereof. After the Pd / Sn / SiO2 is prepared by a step-by-step impregnation method, the Pd / Sn / SiO2 is treated by steam induction at 700-800 DEG C for 3-8 h, thereby breaking through the technical prejudice that traditional "hydrothermal aging leads to performance degradation", and realizing positive regulation of active structure. The obtained catalyst (the actually measured Pd content is only 0.39 wt%) exhibits excellent low-temperature activity (T 50 ≈310 DEG C), long-term stability (70 h without deactivation at 350 DEG C) and water resistance (5% H2O, the activity slightly decreases and can be reversibly recovered within 45 h), and is suitable for efficient purification of low-concentration methane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of environmental catalysis and industrial catalysis, and particularly to a Pd / Sn / SiO2-HTA catalyst, its preparation method, and its applications. Background Technology

[0002] Methane (CH4) is a strong greenhouse gas, with a greenhouse effect potential approximately 23 to 28 times that of CO2. During coal mining, oil and gas processing, and biomass fermentation, large amounts of low-concentration methane are directly emitted into the atmosphere, not only wasting energy but also exacerbating the global greenhouse effect. Catalytic combustion technology can achieve efficient oxidation and conversion of methane at lower temperatures, making it one of the most effective ways to control low-concentration methane emissions. Among numerous catalytic materials, supported palladium (Pd)-based catalysts are widely recognized as the most active catalyst system for methane catalytic combustion due to their excellent activation ability for CH bonds. However, Pd-based catalysts have the following prominent problems in practical applications: (1) insufficient low-temperature activity, as the complete conversion temperature of methane is usually above 400 °C; (2) PdO nanoparticles are prone to sintering and agglomeration under high-temperature conditions, leading to rapid catalyst deactivation; (3) poor resistance to water poisoning, as water vapor in the reaction system adsorbs onto the active sites and reacts with PdO to generate low-activity Pd(OH)2, severely inhibiting catalytic activity and making it difficult to adapt to complex and harsh working environments.

[0003] Extensive research has been conducted on existing technologies to address the aforementioned problems, but significant shortcomings still exist: Related technology one discloses a supported Pd-CeO2-Co3O4 catalyst and its preparation method. This technology uses a hard template method to prepare a CeO2-Co3O4 composite oxide support with a three-dimensional mesoporous structure, and loads Pd active components. However, the catalyst has a high methane ignition temperature, and the preparation process is complex. Related technology two uses titanium silicate molecular sieve TS-1 as a support to load Pt and Pd dual noble metal active components, aiming to improve the catalyst's activity and water resistance. However, the catalyst's activity significantly decreases after hydrothermal aging (700 ℃, 10% H2O, 24 h). In addition, this technology uses a dual noble metal system, which is costly. Related technology three discloses a Pt-doped PdO nanocrystal catalyst and its preparation method. This technology attempts to improve the catalyst's water resistance through the synergistic effect of Pt-Pd bimetals, but its water resistance mechanism depends on the precise control of the Pt / Pd ratio, and the actual water resistance effect is limited.

[0004] Therefore, it is urgent to break through existing technologies and develop a brand-new catalyst design strategy to transform the traditionally recognized "negative factor" (hydrothermal aging) into a "positive control method" to improve the low-temperature activity of the catalyst and fundamentally solve the problems of poor hydrothermal stability and easy water poisoning. Summary of the Invention

[0005] In view of this, the purpose of this invention is to provide a Pd / Sn / SiO2-HTA catalyst, its preparation method, and its application. The Pd / Sn / SiO2-HTA catalyst prepared by this invention exhibits excellent low-temperature activity, long-term stability, and water resistance in the catalytic combustion reaction of methane.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a Pd / Sn / SiO2-HTA catalyst, comprising the following steps: (1) The SiO2 support is subjected to high temperature pretreatment to obtain the high temperature pretreated SiO2 support; (2) The SiO2 support pretreated at high temperature is immersed in a Sn precursor solution, dried, and then subjected to a first calcination to obtain a Sn / SiO2 support; the Sn / SiO2 support comprises a SiO2 support and Sn species loaded on the SiO2 support; the mass of Sn in the Sn precursor solution is 3-15 wt% of the mass of the SiO2 support pretreated at high temperature. (3) The Sn / SiO2 support is impregnated in a Pd precursor solution, dried, and then subjected to a second calcination to obtain Pd / Sn / SiO2; the Pd / Sn / SiO2 comprises a SiO2 support and Sn and Pd species loaded on the SiO2 support; the mass of Pd in ​​the Pd precursor solution is 0.3~1.0 wt% of the mass of the SiO2 support pretreated at high temperature. (4) The Pd / Sn / SiO2 is heated to 450~550 ℃ in air atmosphere and kept at a constant temperature for 10~20 min; the temperature is further increased to 700~800 ℃, and a water vapor atmosphere is introduced at the same time. After reaching the specified temperature, it is kept for 3~8 h to obtain the Pd / Sn / SiO2-HTA catalyst.

[0007] Preferably, in step (1), the temperature of the high-temperature pretreatment is 700~900 ℃ and the time is 4~8 h; the high-temperature pretreatment is carried out in an air atmosphere.

[0008] Preferably, in step (2), the temperature of the first calcination is 700~900 ℃ and the holding time is 4~6 h.

[0009] Preferably, in step (3), the second calcination includes: heating from room temperature to 250-350 ℃ at a heating rate of 2-5 ℃ / min and calcining at a constant temperature for 0.5-2 h, and then continuing to heat to 500-600 ℃ for 2-4 h.

[0010] Preferably, in step (4), the volume fraction of H2O in the water vapor atmosphere is 3~10%.

[0011] Preferably, in step (4), the flow rate of the air atmosphere is 30~80 mL / min.

[0012] Preferably, in step (2), the impregnation is a gradient temperature impregnation; the gradient temperature impregnation includes: increasing the temperature in a water bath at a gradient of 40~70 ℃, and stirring and impregnating for 1 h at every 10 ℃.

[0013] This invention provides a Pd / Sn / SiO2-HTA catalyst prepared by the method described above, comprising a SiO2 support pretreated at high temperature and Sn and Pd species supported on the pretreated SiO2 support; the Sn and Pd species interface forms a Pd-O... latt -Sn active structure; the mass of Sn in the Pd / Sn / SiO2-HTA catalyst is 2~15 wt% of the mass of the SiO2 support pretreated at high temperature, and the mass of Pd is 0.2~1.0 wt% of the mass of the SiO2 support pretreated at high temperature.

[0014] This invention provides the application of the Pd / Sn / SiO2-HTA catalyst described above in the catalytic combustion reaction of low-concentration methane, wherein the CH4 volume fraction in the feed gas is 0.3~1.0%.

[0015] Preferably, the conditions for the catalytic combustion reaction include: a reaction temperature of 200~500 °C and a gas space velocity of 30000~60000 mL / (g). cat The volume fraction of O2 in the feed gas is 3-10%, and the remainder is the balance gas N2.

[0016] This invention provides a method for preparing a Pd / Sn / SiO2-HTA catalyst. The method employs a stepwise impregnation method to prepare Pd / Sn / SiO2, followed by steam-induced treatment at 700-800 °C for 3-8 h. This overcomes the traditional bias that "hydrothermal aging leads to performance degradation" and achieves positive regulation of the active structure. The resulting catalyst exhibits excellent low-temperature activity (T0) in the catalytic combustion of methane. 50 With a temperature range of approximately 310℃, long-term stability (no deactivation at 350℃ for 70 h), and water resistance (slight decrease in activity at 5% H2O for 45 h with reversible recovery), it is suitable for the efficient purification of low-concentration methane. Attached Figure Description

[0017] Figure 1 The methane catalytic combustion activity curves of the catalysts prepared in Example 1 and Comparative Examples 1-3 are shown. Figure 2The results of the 70-h long-term stability test of the catalysts prepared in Example 1 and Comparative Example 1 are shown. Figure 3 The graph shows a comparison of the activities of catalysts with different Sn contents prepared in Examples 1-4 and Comparative Example 2. Figure 4 This is a comparison chart of the activities of catalysts prepared with different types of additives in Example 1 and Comparative Examples 4-5; Figure 5 This is a comparison diagram of the activities of catalysts with different active components prepared in Example 1 and Comparative Example 6; Figure 6 This is a comparison chart of the water resistance stability tests of Example 1 and Comparative Example 1; Figure 7 TEM image of the catalyst prepared in Example 1; Figure 8 TEM image of the catalyst prepared in Comparative Example 1. Detailed Implementation

[0018] This invention provides a method for preparing a Pd / Sn / SiO2-HTA catalyst, comprising the following steps: (1) The SiO2 support is subjected to high temperature pretreatment to obtain the high temperature pretreated SiO2 support; (2) The SiO2 support pretreated at high temperature is immersed in a Sn precursor solution, dried, and then subjected to a first calcination to obtain a Sn / SiO2 support; the Sn / SiO2 support comprises a SiO2 support and Sn species loaded on the SiO2 support; the mass of Sn in the Sn precursor solution is 3-15 wt% of the mass of the SiO2 support pretreated at high temperature. (3) The Sn / SiO2 support is impregnated in a Pd precursor solution, dried, and then subjected to a second calcination to obtain Pd / Sn / SiO2; the Pd / Sn / SiO2 comprises a SiO2 support and Sn and Pd species loaded on the SiO2 support; the mass of Pd in ​​the Pd precursor solution is 0.3~1.0 wt% of the mass of the SiO2 support pretreated at high temperature. (4) The Pd / Sn / SiO2 is heated to 450~550 ℃ in air atmosphere and kept at a constant temperature for 10~20 min; the temperature is further increased to 700~800 ℃, and a water vapor atmosphere is introduced at the same time. After reaching the specified temperature, it is kept for 3~8 h to obtain the Pd / Sn / SiO2-HTA catalyst.

[0019] Unless otherwise specified, all raw materials used in this invention are commercially available products well known in the art.

[0020] The present invention pretreats the SiO2 support at high temperature to obtain a SiO2 support pretreated at high temperature.

[0021] In this invention, the preferred temperature for the high-temperature pretreatment is 700-900 °C, and in specific embodiments, it can be 700, 750, 800, 850, or 900 °C; the preferred duration of the high-temperature pretreatment is 4-8 h, and in specific embodiments, it can be 4, 5, 6, 7, or 8 h; the high-temperature pretreatment is preferably carried out in an air atmosphere. This invention preferably raises the temperature from room temperature to the high-temperature pretreatment temperature, and the preferred heating rate is 5 °C / min. This invention achieves pre-stabilization of the SiO2 support through high-temperature pretreatment, both purifying the surface and strengthening the framework structure through hydroxyl condensation, thus paving the way for the subsequent construction of stable Pd-O. latt -Sn active interface and realize hydrothermal induction effect lay the foundation for carrier.

[0022] After obtaining the SiO2 support pretreated at high temperature, the present invention impregnates the pretreated SiO2 support in a Sn precursor solution, dries it, and then performs a first calcination to obtain the Sn / SiO2 support.

[0023] In this invention, the Sn precursor solution is preferably an aqueous solution of SnCl4·5H2O; the concentration of SnCl4·5H2O in the Sn precursor solution is preferably 0.3~0.5 g / mL.

[0024] In this invention, the mass of Sn in the Sn precursor solution is 3 to 15 wt% of the mass of the SiO2 support pretreated at high temperature. In specific embodiments, it can be 3, 5, 8, 10, 12, 14 or 15 wt%, with the most preferred value being 10 wt%.

[0025] In this invention, the impregnation is preferably a gradient temperature impregnation; the gradient temperature impregnation preferably includes: gradually increasing the temperature in a water bath from 40 to 70 °C, and holding the impregnation with stirring for 1 h at every 10 °C. The reason for using gradient temperature impregnation in this invention is to allow the precursor to slowly, uniformly, and deeply penetrate into the SiO2 channels and form chemical bonds with the carrier surface.

[0026] The present invention does not impose special limitations on the drying conditions; the solution in the impregnation system can be evaporated to dryness. In the embodiments of the present invention, drying is specifically carried out overnight at 80 °C.

[0027] In this invention, the preferred temperature for the first calcination is 700-900 °C, and the preferred holding time is 4-6 h. In specific embodiments, the temperature for the first calcination can be 700, 750, 800, 850, or 900 °C, and the holding time can be 4, 5, or 6 h. In this invention, the heating rate to the first calcination temperature is preferably 2-5 °C / min; the first calcination is preferably carried out in an air atmosphere. This invention converts the Sn precursor into a Sn species anchored onto a SiO2 support through the first calcination. In this invention, the Sn species is SnO2.

[0028] After obtaining the Sn / SiO2 support, the present invention impregnates the Sn / SiO2 support in a Pd precursor solution, dries it, and then performs a second calcination to obtain Pd / Sn / SiO2.

[0029] In this invention, the Pd precursor solution preferably comprises an H2PdCl4 solution. In this invention, the mass of Pd in ​​the Pd precursor solution is 0.3~1.0 wt% of the mass of the SiO2 support pretreated at high temperature; in specific embodiments, it can be 0.3, 0.5, 0.8, or 1.0 wt%, with 0.5 wt% being the most preferred.

[0030] In this invention, the impregnation is preferably carried out with stirring at room temperature, and the impregnation time is preferably 1-3 hours, which can be 2 hours in a specific embodiment. This invention does not impose special limitations on the drying process, as long as excess solvent is removed; in a specific embodiment of this invention, drying is carried out overnight at 80°C.

[0031] In this invention, the second calcination preferably includes: heating from room temperature to 250-350 °C at a heating rate of 2-5 °C / min, specifically to 250, 300, or 350 °C, and calcining at this temperature for 0.5-2 h, for example, 0.5, 1, 1.5, or 2 h, followed by further heating to 500-600 °C, for example, to 500, 550, or 660 °C, and roasting for 2-4 h, for example, 2, 3, or 4 h. This invention converts the Pd precursor solution into Pd species and anchors them on a SiO2 support through the second calcination. In this invention, the Pd species is PdO.

[0032] In this invention, the Pd / Sn / SiO2 includes a SiO2 support and Sn and Pd species loaded on the SiO2 support.

[0033] After obtaining Pd / Sn / SiO2, the present invention heats the Pd / Sn / SiO2 in an air atmosphere to 450-550 °C and holds it at that temperature for 10-20 min; in specific embodiments, the temperature can be raised to 450, 500, or 550 °C and held at that temperature for 10, 15, or 20 min. In the present invention, the flow rate of the air atmosphere is preferably 30-80 mL / min, and in specific embodiments, it can be 30, 40, 50, 60, 70, or 80 mL / min, with 50 mL / min being the most preferred. The present invention preferably heats the Pd / Sn / SiO2 from room temperature to 450-550 °C; the heating rate is preferably 5-10 °C / min. The present invention first calcines the Pd / Sn / SiO2 in an air atmosphere at 450-550 °C for 10-20 min to purify the catalyst surface, ensure the integrity of the PdO phase, and provide a stable and controllable starting state for subsequent water vapor induction.

[0034] Next, the temperature is further increased to 700-800 °C, and a water vapor atmosphere is introduced simultaneously with the temperature increase. After reaching the specified temperature, the temperature is maintained for 3-8 h to obtain the Pd / Sn / SiO2-HTA catalyst. In this invention, the preferred rate of further heating is 5-10 °C / min. In specific embodiments, the temperature can be increased to 700, 750, or 800 °C, with 750 °C being the most preferred, and maintained for 3, 4, 5, 6, 7, or 8 h. In this invention, the volume fraction of H2O in the water vapor atmosphere is preferably 3-10%, and in specific embodiments, it can be 3%, 5%, 6%, 7%, 8%, or 10%. In this invention, the carrier gas for the water vapor atmosphere is preferably air. The water vapor atmosphere is preferably generated by a bubbling method.

[0035] This invention constructs a Pd-O catalyst by forming a Pd-Sn interface on the catalyst surface through hydrothermal induction treatment. latt -Sn active structure, where "O" latt "Refers to lattice oxygen."

[0036] This invention provides a Pd / Sn / SiO2-HTA catalyst prepared by the method described above, comprising a SiO2 support pretreated at high temperature and Sn and Pd species supported on the pretreated SiO2 support; the Sn and Pd species interface forms a Pd-O... latt -Sn active structure; the mass of Sn in the Pd / Sn / SiO2-HTA catalyst is 2~15 wt% of the mass of the SiO2 support pretreated at high temperature, and the mass of Pd is 0.2~1.0 wt% of the mass of the SiO2 support pretreated at high temperature.

[0037] The catalyst prepared in this invention uses high-temperature pretreated SiO2 as a support, Sn as a promoter, and Pd as the active component. A Pd-Sn interface is formed on the catalyst surface through high-temperature steam-induced treatment, thereby constructing a Pd-O... latt The -Sn highly active structure makes the catalyst, used in the catalytic combustion of methane, exhibiting excellent low-temperature activity, long-term stability, and water resistance.

[0038] This invention provides the application of the Pd / Sn / SiO2-HTA catalyst described above in the catalytic combustion reaction of low-concentration methane, wherein the volume fraction of CH4 in the feed gas is 0.3~1.0%, and in specific embodiments it can be 0.3%, 0.5%, 0.6%, 0.8% or 1.0%.

[0039] In this invention, the preferred conditions for the catalytic combustion reaction include: a reaction temperature of 200-500 °C and a gas space velocity of 30,000-60,000 mL / (g). cat The feed gas contains 3-10% O2 by volume, with the remainder being N2 as the equilibrium gas. In specific embodiments, the reaction temperature can be 200, 300, 400, or 500 °C, and the gas hourly space velocity can be 30,000, 40,000, 50,000, or 60,000 mL / (g·h). cat The volume fraction of O2 in the feed gas can be 3%, 5%, 7% or 10%.

[0040] The following examples illustrate the Pd / Sn / SiO2-HTA catalyst, its preparation method, and its applications provided by this invention. However, these examples should not be construed as limiting the scope of protection of this invention.

[0041] The commercial SiO2 used in the following examples and comparative examples was purchased from Sinopharm Chemical Reagent Co., Ltd., model N20, with analytical grade (AR).

[0042] Example 1 Preparation of Pd / 10%Sn / SiO2-HTA catalyst (1) Pretreatment of SiO2 support: Commercial SiO2 was placed in a muffle furnace and heated from room temperature to 800 ℃ at a heating rate of 5 ℃ / min. It was calcined at a constant temperature for 6 h and then naturally cooled to room temperature for later use.

[0043] (2) Preparation of Sn / SiO2 support: Dissolve 3.0 g SnCl4·5H2O in 10 mL of deionized water and stir thoroughly until completely dissolved; take 1 mL of the solution and place it in a beaker, add 1 g of SiO2 pretreated in step (1), and stir thoroughly; place the beaker in a water bath and gradually increase the temperature from 40 °C to 70 °C, stopping at 10 °C for stirring and soaking for 1 h; then place it in a drying oven and dry at 80 °C overnight; finally transfer it to a muffle furnace and raise the temperature from room temperature to 800 °C at a rate of 5 °C / min, calcine at a constant temperature for 5 h, and cool naturally to obtain 10% Sn / SiO2 support.

[0044] (3) Preparation of Pd / 10%Sn / SiO2 catalyst: Take 0.25 mL of H2PdCl4 solution (containing 0.5 wt% Pd) and place it in a beaker. Add 1 mL of deionized water and stir thoroughly. Add 1 g of the 10% Sn / SiO2 support prepared in step (2) and stir and impregnate at room temperature for 2 h. Place it in a drying oven and dry at 80 ℃ overnight. Then transfer it to a muffle furnace and heat it from room temperature to 300 ℃ at a heating rate of 2 ℃ / min and calcine it at a constant temperature for 1 h. Then continue to heat it to 550 ℃ and calcine it for 3 h to obtain Pd / 10%Sn / SiO2 catalyst.

[0045] (4) Hydrothermal induction treatment: The catalyst obtained in step (3) was placed in a tube furnace and heated from room temperature to 500 ℃ at a rate of 8 ℃ / min under an air atmosphere (flow rate of 50 mL / min) and held at that temperature for 15 min; the temperature was further increased to 750 ℃, and 5 vol% H2O (generated by bubbling method, with air as the carrier gas) was added and held for 5 h; the temperature was then naturally cooled to room temperature to obtain the Pd / 10%Sn / SiO2-HTA catalyst. The actual Pd content in the catalyst was measured to be 0.39 wt% by ThermoICAPPRO inductively coupled plasma optical emission spectrometry (ICP-OES).

[0046] Catalytic performance test: 0.1 g of catalyst (40~60 mesh) was loaded into a fixed-bed quartz reaction tube, and the feed gas was introduced: 0.5 vol% CH4, 5 vol% O2, with the balance being N2, GHSV = 50000 mL / (g) cat •h). The temperature was increased from 200 °C to 500 °C at a rate of 2 °C / min, and samples were taken for analysis at regular temperature intervals. The reaction products were analyzed online by gas chromatography (TCD detector).

[0047] Test result: T 50 =310 ℃, T 90 =348 ℃.

[0048] Example 2 Preparation of Pd / 3%Sn / SiO2-HTA catalyst The preparation method is the same as in Example 1, except that the amount of SnCl4·5H2O in step (2) is adjusted to 0.9 g, so that the theoretical loading of Sn is 3 wt%.

[0049] Test result: T 50 =345 ℃, T 90 =382 ℃.

[0050] Example 3 Preparation of Pd / 5%Sn / SiO2-HTA catalyst The preparation method is the same as in Example 1, except that the amount of SnCl4·5H2O in step (2) is adjusted to 1.5 g, so that the theoretical loading of Sn is 5 wt%.

[0051] Test result: T 50 =336 ℃, T 90 =380 ℃.

[0052] Example 4 Preparation of Pd / 15%Sn / SiO2-HTA catalyst The preparation method is the same as in Example 1, except that the amount of SnCl4·5H2O in step (2) is adjusted to 4.5 g, so that the theoretical loading of Sn is 15 wt%.

[0053] Test result: T 50 =341 ℃, T 90 =387 ℃.

[0054] Example 5 Preparation of Pd / 10%Sn / SiO2-HTA (1h) catalyst The preparation method is the same as in Example 1, except that the hydrothermal induction treatment time in step (4) is adjusted to 1 h.

[0055] Test result: T 50 =320 ℃, T 90 =375 ℃.

[0056] Example 6 Preparation of Pd / 10%Sn / SiO2-HTA (3h) catalyst The preparation method is the same as in Example 1, except that the hydrothermal induction treatment time in step (4) is adjusted to 3 h.

[0057] Test result: T 50 =315 ℃, T 90 =358 ℃.

[0058] Example 7 Preparation of Pd / 10%Sn / SiO2-HTA (8h) catalyst The preparation method is the same as in Example 1, except that the hydrothermal induction treatment time in step (4) is adjusted to 8 h.

[0059] Test result: T 50 =355 ℃, T 90 =352 ℃.

[0060] Comparative Example 1 Preparation of Pd / 10%Sn / SiO2 catalyst (hydrothermal induction treatment) The preparation method is the same as in Example 1, but the hydrothermal induction treatment in step (4) is omitted. The actual Pd content in the catalyst was measured to be 0.43 wt% by ICP-OES.

[0061] Test result: T 50 =350 ℃, T 90 =383 ℃.

[0062] Comparative Example 2 Preparation of Pd / SiO2-HTA catalyst (without Sn promoter) The preparation method was the same as in Example 1, but step (2) was omitted, and Pd was directly loaded onto the pretreated SiO2 support. The actual Pd content in the catalyst was measured to be 0.44 wt% by ICP-OES.

[0063] Test result: T 50 =368 ℃, T 90 =425 ℃.

[0064] Comparative Example 3 Preparation of Pd / SiO2 catalyst (without Sn promoter and without hydrothermal induction treatment) The preparation method is the same as in Example 1, but step (2) is omitted, and Pd is directly loaded onto the pretreated SiO2 support, and the hydrothermal induction treatment in step (4) is omitted. The actual Pd content in the catalyst was measured to be 0.39 wt% by ICP-OES.

[0065] Test result: T 50 =361℃, T 90 =400 ℃.

[0066] Comparative Example 4 Preparation of Pd / 10%Ce / SiO2-HTA catalyst The preparation method is the same as in Example 1, except that SnCl4·5H2O is replaced with Ce(NO3)3·6H2O in step (2) so that the theoretical loading of Ce is 10 wt%.

[0067] Test result: T 50 =364 ℃, T 90 =411 ℃.

[0068] Comparative Example 5 Preparation of Pd / 10%Zr / SiO2-HTA catalyst The preparation method is the same as in Example 1, except that SnCl4·5H2O is replaced with Zr(NO3)4·5H2O in step (2) so that the theoretical loading of Zr is 10 wt%.

[0069] Test result: T 50 =404 ℃, T 90 =490 ℃.

[0070] Comparative Example 6 Preparation of Pt / 10%Sn / SiO2-HTA catalyst The preparation method is the same as in Example 1, except that in step (3), the H2PdCl4 solution is replaced with H2PtCl6 solution so that the theoretical loading of Pt is 0.5 wt%.

[0071] Figure 1 The methane catalytic combustion activity curves of the catalysts prepared in Example 1 and Comparative Examples 1-3 are shown. In this example, Pd / Sn / SiO2-HTA represents Example 1, Pd / Sn / SiO2 represents Comparative Example 1, Pd / SiO2-HTA represents Comparative Example 2, and Pd / SiO2 represents Comparative Example 3. Figure 3 This is a comparison chart of the activities of catalysts with different Sn contents prepared in Examples 1-4 and Comparative Example 2. Figure 4 This is a comparison chart of the activities of catalysts prepared with different types of additives in Example 1 and Comparative Examples 4-5; Figure 5 This is a comparison chart of the activities of the catalysts with different active components prepared in Example 1 and Comparative Example 6. Specific activity test results are summarized in Table 1.

[0072] Table 1. Composition and activity test results of catalysts prepared in Examples 1-7 and Comparative Examples 1-6

[0073] Note: Due to the poor catalyst activity of Comparative Example 6, the methane conversion rate did not reach 50% within the test temperature range, therefore no T was specified. 50 This data is provided for clarification.

[0074] The test results in Table 1 show that: (1) Positive promoting effect of hydrothermal induction treatment on activity: Comparative Example 1 (Pd / 10%Sn / SiO2, without hydrothermal treatment) T 50 The temperature was 350 °C, while in Example 1, after hydrothermal induction treatment for 5 hours, T 50 The temperature was significantly reduced to 310 °C, while the activity increased by approximately 40 °C. This result clearly demonstrates that high-temperature steam treatment does not lead to performance degradation, but rather can actively construct a highly active structure, achieving the technical effect of "hydrothermal promotion." This contrasts sharply with the common pattern in related technologies where activity decreases by 10 to 100 °C after hydrothermal aging, and is the biggest highlight of this invention.

[0075] (2) Effect of Sn content: Examples 2-4 investigated the effect of different Sn loadings (3%, 5%, 15%) on catalytic performance. The results showed that as the Sn content increased, the activity exhibited a volcano-like trend of first increasing and then decreasing, with the best activity observed when the Sn loading was 10% (Example 1). When the Sn content was too low (3%), the number of Pd-Sn interfaces was insufficient, making it difficult to effectively regulate the active structure; when the Sn content was too high (15%), it may cover some Pd active sites or block the pores of the support, leading to a decrease in activity.

[0076] (3) Effect of hydrothermal induction time: Examples 5-7 investigated the effect of different hydrothermal induction times (1h, 3h, 8h). The results showed that the activity gradually increased with the extension of treatment time, but the activity decreased slightly with excessively long treatment times. When treated for 1h (Example 5), T 50 The activity increased at 320 °C, indicating that Pd-O latt -Sn active structure gradually forms; during treatment for 3 hours (Example 6) and 5 hours (Example 1), T 50 The temperatures were 315℃ and 310℃, respectively, indicating that Pd-O latt - The active structure of Sn has been optimized; when the activity was extended to 8 hours (Example 7), the activity decreased slightly, which may be due to the deterioration of the SiO2 texture.

[0077] (4) Screening of additive types: Comparative examples 4-5 were subjected to hydrothermal induction treatment with Ce and Zr replacing Sn, respectively. The results showed that Pd / 10%Ce / SiO2-HTA (T 50 =364℃) and Pd / 10%Zr / SiO2-HTA (T 50 =404 ℃) The activity of Pd / 10%Sn / SiO2-HTA (T =404 ℃) is significantly lower than that of Pd / 10%Sn / SiO2-HTA (T 50 =310 ℃), indicating that Sn is the optimal auxiliary agent for constructing a highly active interface structure with Pd. This may be attributed to Sn's suitable redox properties and ionic radius, which enable it to form a stable Pd-O-Sn bond structure with PdO, promoting lattice oxygen activation.

[0078] (5) Screening of active metals: Comparative Example 6 used Pt instead of Pd as the active metal. The results showed that the activity of Pt / 10%Sn / SiO2-HTA was much lower than that of Pd-based catalysts, indicating that Pd is the most preferred active metal for the catalytic combustion reaction of methane.

[0079] Long-term stability tests were conducted on the catalysts of Example 1 and Comparative Example 1 at 350 °C for 70 h. The specific test procedure was as follows: 0.1 g of catalyst (40-60 mesh) was loaded into a fixed-bed quartz reaction tube, and a feed gas mixture of 0.5 vol% CH4, 5 vol% O2, and the remainder N2 was introduced, with GHSV = 50000 mL / (g). cat •h). The temperature was increased from 200 °C to 350 °C at a rate of 2 °C / min and held for 70 h. The results are as follows: Figure 2 As shown. By Figure 2 It can be seen that the methane conversion rate of Example 1 remained at around 80%, while Comparative Example 1 (without hydrothermal treatment) gradually deactivated from 37 h, and the methane conversion rate gradually decreased from the initial 50% to 30%.

[0080] Water resistance tests (400℃, 5% H2O, 45 h) showed that the activity of Example 1 decreased only slightly after water was introduced and recovered rapidly after water removal; while the activity of Comparative Example 1 decreased after water introduction, and the activity decreased again by about 10% after 8 hours of water introduction. Figure 6 As shown in the figure, this fully demonstrates that the strong Pd-Sn interaction constructed by hydrothermal induction treatment can effectively inhibit the adsorption and dissociation of H2O on Pd active sites and prevent the formation of low-activity Pd(OH)2.

[0081] The catalyst prepared in Example 1 was observed by transmission electron microscopy (TEM), and the results are as follows: Figure 7 As shown, by Figure 7 Pd-O can be clearly observed latt -Sn interface; TEM observation was performed on the catalyst prepared in Comparative Example 1, and the results are as follows: Figure 8 As shown, by comparing the transmission electron microscope images of Example 1 and Comparative Example 1, it can be observed that Comparative Example 1 did not form Pd-O. latt -Sn interface. This result indicates that water vapor-induced treatment led to the formation of a Pd-O interface on the catalyst surface. latt -Sn interface.

[0082] As can be seen from the results of the above embodiments and comparative examples, the present invention uses SiO2, which has high hydrothermal stability, as a support and Sn, which is beneficial for inhibiting water vapor poisoning, as an auxiliary agent to prepare a Pd / Sn / SiO2 catalyst by a stepwise impregnation method, and then constructs a Pd-O2 catalyst on the catalyst surface through high-temperature steam-induced treatment. latt-Sn highly active interface structure. This catalyst exhibits excellent low-temperature activity (T0) in the catalytic combustion of methane. 50 The catalyst exhibits excellent performance characteristics, including high-temperature steam treatment (310 °C), long-term stability (no deactivation at 350 °C for 70 h), and water resistance (slight decrease in activity with reversible recovery after 45 h under 5% H2O). This invention overcomes the traditional bias that "hydrothermal aging leads to catalyst performance degradation," transforming high-temperature steam treatment from a "durability evaluation method" to an "activity structure regulation method." It provides a novel approach for preparing highly efficient and economical Pd-based catalysts, showing broad industrial application prospects in the purification of low-concentration methane and contributing to the achievement of dual-carbon goals.

[0083] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a Pd / Sn / SiO2-HTA catalyst, characterized in that, Includes the following steps: (1) The SiO2 support is subjected to high temperature pretreatment to obtain the high temperature pretreated SiO2 support; (2) The SiO2 support pretreated at high temperature is immersed in a Sn precursor solution, dried, and then subjected to a first calcination to obtain a Sn / SiO2 support; the Sn / SiO2 support comprises a SiO2 support and Sn species loaded on the SiO2 support; the mass of Sn in the Sn precursor solution is 3-15 wt% of the mass of the SiO2 support pretreated at high temperature. (3) The Sn / SiO2 support is impregnated in a Pd precursor solution, dried, and then subjected to a second calcination to obtain Pd / Sn / SiO2; the Pd / Sn / SiO2 comprises a SiO2 support and Sn and Pd species loaded on the SiO2 support; the mass of Pd in ​​the Pd precursor solution is 0.3~1.0 wt% of the mass of the SiO2 support pretreated at high temperature. (4) The Pd / Sn / SiO2 is heated to 450~550 ℃ in air atmosphere and kept at a constant temperature for 10~20 min; the temperature is further increased to 700~800 ℃, and a water vapor atmosphere is introduced at the same time. After reaching the specified temperature, it is kept for 3~8 h to obtain the Pd / Sn / SiO2-HTA catalyst.

2. The preparation method according to claim 1, characterized in that, In step (1), the temperature of the high-temperature pretreatment is 700~900 ℃ and the time is 4~8 h; the high-temperature pretreatment is carried out in an air atmosphere.

3. The preparation method according to claim 1, characterized in that, In step (2), the temperature of the first calcination is 700~900 ℃, and the holding time is 4~6 h.

4. The preparation method according to claim 1, characterized in that, In step (3), the second calcination includes: heating from room temperature to 250-350 ℃ at a heating rate of 2-5℃ / min and calcining at a constant temperature for 0.5-2 h, and then continuing to heat to 500-600℃ for calcination for 2-4 h.

5. The preparation method according to claim 1, characterized in that, In step (4), the volume fraction of H2O in the water vapor atmosphere is 3~10%.

6. The preparation method according to claim 1, characterized in that, In step (4), the flow rate of the air atmosphere is 30~80 mL / min.

7. The preparation method according to claim 1, characterized in that, In step (2), the impregnation is a gradient temperature impregnation; the gradient temperature impregnation includes: increasing the temperature in a water bath at a gradient of 40~70 ℃, and stirring and impregnating for 1 h at every 10 ℃.

8. The Pd / Sn / SiO2-HTA catalyst prepared by the method according to any one of claims 1 to 7 comprises a SiO2 support pretreated at high temperature and Sn and Pd species supported on the pretreated SiO2 support; wherein the Sn and Pd species interface forms a Pd-O2 bond. latt -Sn active structure; the mass of Sn in the Pd / Sn / SiO2-HTA catalyst is 2~15wt% of the mass of the SiO2 support pretreated at high temperature, and the mass of Pd is 0.2~1.0wt% of the mass of the SiO2 support pretreated at high temperature.

9. The application of the Pd / Sn / SiO2-HTA catalyst according to claim 8 in the catalytic combustion reaction of low-concentration methane, wherein the volume fraction of CH4 in the feed gas is 0.3~1.0%.

10. The application according to claim 9, characterized in that, The conditions for the catalytic combustion reaction include: a reaction temperature of 200–500 °C and a gas space velocity of 30,000–60,000 mL / (g). cat The volume fraction of O2 in the feed gas is 3-10%, and the remainder is the balance gas N2.